2010
DOI: 10.1161/strokeaha.109.573618
|View full text |Cite
|
Sign up to set email alerts
|

Recent Nationwide Trends in Discharge Statin Treatment of Hospitalized Patients With Stroke

Abstract: Background and Purpose-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 26 publications
8
38
1
Order By: Relevance
“…The increasing use of antihyperlipidemic therapy in patients with coronary artery disease and stroke has resulted in a reduction in total atherosclerosis burden. 13,14 Furthermore, there has been a reported growth in the use of physiological screening tools for peripheral arterial disease, 15 which may allow earlier identification of individuals with subclinical critical limb ischemia. The positive impact of surveillance imaging programs on graft patency has also been recognized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing use of antihyperlipidemic therapy in patients with coronary artery disease and stroke has resulted in a reduction in total atherosclerosis burden. 13,14 Furthermore, there has been a reported growth in the use of physiological screening tools for peripheral arterial disease, 15 which may allow earlier identification of individuals with subclinical critical limb ischemia. The positive impact of surveillance imaging programs on graft patency has also been recognized.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of surgical bypass showed a significant reduction between the first and second decades (36.6% versus 29.6%, respectively; P<0.0001), whereas the rates of catheter-based thrombolysis increased significantly for the same decade comparison (4.6% versus 7.1%, respectively; Age, mean (SD), y* 68 (14) 66 (13) 70 (14) 67 (14) 65 (14) 70 ( …”
Section: Methodsmentioning
confidence: 99%
“…For example, statin medications (3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors) are among the most commonly used medications for secondary prevention of ischemic stroke. [20][21][22][23] Several observational studies in nonstroke patient populations have reported a protective effect for statins in that prior use results in reduced risk for developing an infection. [24][25][26][27] These results are interpreted to indicate that immunomodulation and peripheral anti-inflammatory properties are among the beneficial pleiotropic actions of statins that may inhibit a proinflammatory environment favoring infection.…”
Section: Introductionmentioning
confidence: 99%
“…When office blood pressure values were examined no significant differences were observed between PCP encounters and neurologist encounters suggesting that either blood pressure level during was not the main driver of the higher antihypertensive drug use seen among PCPs or patient blood pressure levels were higher in the PCP group thereby stimulating a higher treatment rate. While several studies have reported that neurologistā€™s management, compared with generalistā€™s management, is associated with improved patient outcomes among hospitalized stroke patients, 18-22 and there are data on the influence of recent clinical trials on inpatient treatment rates, 23 few comparisons have been conducted in the ambulatory care setting. 24 Patients and neurologists seem to generally perceive that neurologic outpatient involvement adds value to care, 25 but more objective data to support this notion are lacking.…”
Section: Discussionmentioning
confidence: 99%